Internal marketing management in Ukrainian chained-brand hotels - Kravtsov, Sergiy (Baltija Publishing, 2017)
The purpose of this scientific research is clarification of the level of importance of the internal marketing activity in chained-brand hotels and recognizing of the effectiveness of the internal marketing functioning in these enterprises. Метою даного наукового дослідження є з'ясування рівня важливості внутрішньої маркетингової діяльності в мережевих готелях та визначення ефективності внутрішнього маркетингу для функціонування цих підприємств.
Keywords: internal marketing; chained-brand hotels; internal marketing program; внутрішній маркетинг; мережеві готелі; програма з внутрішнього маркетингу; кафедра туристичного та готельного бізнесу